Leading Political Parties Experience: the role of Organizational-Legal and Ideological Aspects in Party Activity - Bekzod Najmiddinov (Genius Journals, 2023)
First of all, it is of utmost importance to thoroughly analyze the comprehensive functions of the political parties prior to assess their activities. Such kind of analysis reveal that there has not been carried out enough research to study the experience of leading political parties in developed countries and to introduce some of their aspects in the activities of our parties. The experience of leading political parties is an essential means for parties functioning in any country of the world. The experience of leading parties can be helpful for political parties that are just about to start their activities or for those that are encountering a number of critical issues, and can motivate them to reconsider and adjust their actions. While studying the leading foreign experience, it is crucial, firstly, to determine which aspects should be focused on. In fact, the experience in every area has to be researched and studied while studying the experience of political parties operating comprehensively. However, current research covers the organizational, legal, and ideological features that have led political parties to take a leading position in developed countries around the world
Keywords: have; parties; features; position